ANALISIS PROFITABILITAS, LIKUIDITAS DAN EFISIENSI TERHADAP RETURN SAHAM PADA PERUSAHAAN PERBANKAN DI BURSA EFEK INDONESIA - Shellim, Fenny; Banjarnahor, Haposan (SCIENTIA JOURNAL, 2021)
The main purpose of this research is to find out the effect of Return on Equity, Loan to Deposit Ratio, and Operating Expenses to Operating Incomes to stock return. Population of this research consisted 45 banking companies on Indonesia Stock Exchange. Sampling techniques use purposive sampling and got 32 companies that passed the specified sampling criteria. Data collection techniques using documentation techniques. The result of hypothesis which used t test shows that Return on Equity has no significant effect on stock return with t count 0.152 < t table 1.98045 with significance 0.880 > 0.05, loan to deposit ratio has no significant effect on stock return with t count -1.206 > t table -1.98045 with significance 0.230 > 0.05, and Operating Expenses to Operating Incomes has a negative effect on stock return with t count < t table that is -2.435 < -1.98045 with the significance level 0.016 < 0.05. While the result of hypothesis using F test show that Return on Equity, Loan to Deposit Ratio, and OEOI simultaneously influence to stock return with f count 7.081 > f table 2.68 with significance 0.000 < 0.05.